Phenotypic Heterogeneity of Breast Cancer Stem Cells. (2nd January 2011) - Lorico, Aurelio; Rappa, Germana
Abstract : Many types of tumors are organized in a hierarchy of heterogeneous cell populations, with only a small proportion of cancer stem cells (CSCs) capable of sustaining tumor formation and growth, giving rise to differentiated cells, which form the bulk of the tumor. Proof of the existence of CSC comes from clinical experience with germ-cell cancers, where the elimination of a subset of undifferentiated cells can cure patients (Horwich et al., 2006), and from the study of leukemic cells (Bonnet and Dick, 1997; Lapidot et al., 1994; and Yilmaz et al., 2006). The discovery of CSC in leukemias as well as in many solid malignancies, including breast carcinoma (Al-Hajj et al. 2003; Fang et al., 2005; Hemmati et al., 2003; Kim et al., 2005; Lawson et al., 2007; Li et al., 2007; Ricci-Vitiani et al., 2007; Singh et al., 2003; and Xin et al., 2005), has suggested a unifying CSC theory of cancer development. The reported general insensitivity of CSC to chemotherapy and radiation treatment (Bao et al., 2006) has suggested that current anticancer drugs, which inhibit bulk replicating cancer cells, may not effectively inhibit CSC. The clinical relevance of targeting CSC-associated genes is supported by several recent studies, including CD44 targeting for treatment of acute myeloid leukemia (Jin et al., 2006), CD24 targeting for treatment of colon and pancreatic cancer (Sagiv et al., 2008), and CD133 targeting for hepatocellular and gastric cancer (Smith et al., 2008). One promising approach is to target CSC survival signaling pathways, where leukemia stem cell research has already made some progress (Mikkola et al., 2010).